Inguinal draining-lymph node in 18F-FDG PET/CT images could be a new indicator for the diagnosis of fracture-related infection in the lower extremities - Wang, Yanbing; Sun, Zhenkui; Liang, Xiao; Shen, Chentian (Frontiers in Immunology, 2023)
Purpose The imaging diagnosis of fracture-related infection is often challenging. The aim of this study was to evaluate the value of 18F-FDG PET/CT for the diagnosis of fracture-related infection (FRI) with internal fixation after orthopedic surgery in lower extremities. Methods A total of 254 consecutive patients who underwent 18F-FDG PET/CT scans with suspected FRI with internal fixation in lower extremities were retrospectively investigated 18F-FDG PET/CT images were semiquantitatively evaluated with multiple metabolic parameters. Additionally, morphological information of the inguinal draining lymph nodes (DLN) with the highest SUV value was also collected and analyzed. Results Patients were divided into two groups according to final diagnosis: the infected (N=197) and the non-infected group (N=57). The differences in the inguinal DLN-related parameters, including the long diameter, short diameter, maximum cross-sectional area, maximum standardized uptake value (SUVmax), metabolic volume (MV) 60%, MV70%, MV80%, total lesional glycolysis (TLG) 60%, TLG70%, TLG80%, and the infection suspected area related parameters, including SUVmax, MV25%, MV30%, MV35%, MV40%, MV50%, and TLG70%, between the two groups were statistically significant. We then compared the highest area under the curves (AUCs) among the morphological parameters of DLN, metabolic parameters of DLN, and metabolic parameters of the suspected infection area. The result demonstrated that SUVmax of the inguinal DLN showed the best diagnostic performance with an AUC of 0.939 (P<0.05). Conclusion Semiquantitative analysis (especially SUVmax) of the inguinal DLN in 18F-FDG PET/CT images could be a promising method for the diagnosis of suspected FRI with internal fixation after orthopedic surgery in lower extremities.